Protein Kinase CK-1 Inhibitors As New Potential Drugs for Amyotrophic Lateral Sclerosis. - Salado, I.G.; Redondo, M.; Bello, M.L.; Perez, C.; Liachko, N.F.; Kraemer, B.C.; Miguel, L.; Lecourtois, M.; Gil, C.; Martinez, A.; Perez, D.I. (Journal of Medicinal Chemistry, 2014)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease where motor neurons in cortex, brain stem, and spinal cord die progressively, resulting in muscle wasting, paralysis, and death. Currently, effective therapies for ALS are lacking; however, identification of pathological TAR DNA-binding protein 43 (TDP-43) as the hallmark lesion in sporadic ALS suggests new therapeutic targets for pharmacological intervention. Pathological TDP-43 phosphorylation appears to drive the onset and progression of ALS and may result from upregulation of the protein kinase CK-1 in affected neurons, resulting in postranslational TDP-43 modification. Consequently, brain penetrant specific CK-1 inhibitors may provide a new therapeutic strategy for treating ALS and other TDP-43 proteinopathies. Using a chemical genetic approach, we report the discovery and further optimization of a number of potent CK-1? inhibitors. Moreover, these small heterocyclic molecules are able to prevent TDP-43 phosphorylation in cell cultures, to increase Drosophila lifespan by reduction of TDP-43 neurotoxicity, and are predicted to cross the blood-brain barrier. Thus, N-(benzothiazolyl)-2-phenyl-acetamides are valuable drug candidates for further studies and may be a new therapeutic approach for ALS and others pathologies in which TDP-43 is involved.